Influencing consumers' trust in online grocery shopping: a survey among Malaysian / Mohd Remie Mohd Johan ... [et al.] - Mohd Johan, Mohd Remie; Shao, Zhucheng; Lim, Kelly Qiao Ling; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2022)
In Malaysia, online grocery shopping is an emerging field where consumer trust has become a key factor affecting its growth and prosperity. Although grocery shopping does not account for a significant share of total consumer spending, it plays an irreplaceable role due to its unique characteristics of perishability and variability, which makes it relevant to consumers' quality of life. This article aims to explore false advertising, quality issues, logistics, and reputation concerning consumer trust in grocery shopping, using non-probability sampling research techniques in 390 questionnaires from consumers aged between 18 and 45. This article finds that false advertising and logistics have little direct association with consumer trust, while quality issues and reputation have a positive impact on consumer trust in online grocery shopping. Our study fills a gap in this area at this stage and makes further recommendations to the government, online shopping platforms, and grocers, to strengthen their regulation, purify the business activities in the market, and promote the growth and prosperity of online grocery shopping in Malaysia in light of this research finding.